Oxytocin administration is a potential tool for behavioral management in felids - Burkhart, Jessica C.; Heilbronner, Sarah R.; Packer, Craig (Frontiers in Mammal Science, 2023)
Living in a group setting is essential for the health and wellbeing of social carnivores; however, the managed formation of captive groups of territorial animals can be challenging because of the risk of aggression, injury, and even death. Numerous laboratory and clinical studies have implicated oxytocin in the formation of social bonds. Previously, we have shown that oxytocin (OT) administration reduced social vigilance in African lions. Here, we describe a series of case reports in which OT administration was used to facilitate social bonding in both familiar and unfamiliar conspecific pairs and groups of African lions and tigers, and we provide qualitative descriptions of the study animals’ behaviors before and after treatment. We hypothesized that the repeated intranasal administration of oxytocin over a period of 6–8 weeks would facilitate (1) the bonding process during introductions of unfamiliar individuals and (2) reconciliation between paired individuals that had developed ongoing negative social relationships. Following OT treatment, positive social interactions were either observed for the first time or were restored in all seven study groups.